Two Epileptic Death Cases with Postmortem Diagnosis: Tuberosclerosis Complex - Ketenci, Hüseyin Çetin; Çakır, Emel; Demir, İbrahim and Beyhun, Nazım Ercüment (The Bulletin of Legal Medicine, 2017)
Tuberous sclerosis complex is an autosomal dominant disorder characterized by skin manifestations and formation of multiple benign tumors in different organs such as brain, kidneys, heart, liver, eyes and lungs. Two 15 years old females who had epilepsy for a long time were diagnosed TSC by autopsy performed in Forensic Medicine Institute. In this study, we aim that emphasize the importance of ‘medical autopsy’ to diagnose TSC and discuss this rare disorder which have only epilepsy in patient’s medical history in forensic medicine practice via current literature.